Rasa Insecure Pada Remaja Terhadap Hubungan Sosialnya (International Forum of Researchers and Lecturers, 2024)
Insecurity is a situation where a person has feelings of discomfort, this is felt bye individuals who lack self confidence, are anxious, pessimitics, depressed and feel like they are always wrong. The purpose of the research is to find out how much insecurity exists in teenagers. This research method uses quantitative methods with a directive counseling approach. Based on research results, this feeling of insecurity is experienced by many teenagers aged 11-21 years and this insecurity is very dominant among women because they have a higher level of sensitivity to what is around them and they also like to compare the contents of themselves. with the achievements of other individuals, that's why they often don't feel enough about themselves. Therefore, a mindset as well as support and the surrounding environment are also really needed here so that feelings of insecurity can be reduced and eventually disappear and teenagers can freely believe in what is in themselves.